A screening for optimal selenium enrichment additives for selenium-enriched fish production: Application of a HPLC-ICP-MS method - Chao Zhu; Qimin Liu; Yang Wang; Xiaolin Wang; Yuxuan Ma; Fangxia Yang; Wuzi Dong; Hong Ji (Food Chemistry: X, 2024)
The production of selenium-enriched fish contributes to alleviating selenium deficiency for humans. In this study, selenium nanoparticles (SeNPs) comparable in bioavailability to selenomethionine (SeMet), increased SeMet content in O. macrolepis (Onychostoma macrolepis) muscle. Additionally, dietary SeNPs significantly enhanced selenocysteine (SeCys2) and methylselenocysteine (MeSeCys) levels in O. macrolepis muscle. The effect of SeNPs on selenium speciation in grass carp muscle was consistent with O. macrolepis results. SeCys2 and MeSeCys showed antioxidant capacity in HEK293T cells, indicating enhanced health benefits of Se-enriched fish produced using SeNPs. Furthermore, the addition of 0.3 mg/kg SeNPs significantly improved the flesh quality of O. macrolepis by reducing the content of crude fat and heavy metals, as well as increasing the levels of crude protein, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and the ratio of n-3/n-6 polyunsaturated fatty acids (PUFAs). Therefore, selenium-enriched fish produced from SeNPs is a good source for improving human dietary selenium intake.